Induction of genomic instability in a primary human fibroblast cell line following low-dose alpha-particle exposure and the potential role of exosomes - Elbakrawy, E; Mayah, A; Hill, M; Kadhim, M (MDPI, 2020)
Purpose: To study the induction of genomic instability (GI) in the progeny of cell populations irradiated with low doses of alpha-particles and the potential role of exosome-encapsulated bystander signalling.